Facets of Mathematics Education towards Achieving Mathematics Competence in Children - Lal, Dori; Batra, Rakesh; Rani, Neeta (JOURNAL OF INDIAN EDUCATION, 2022)
Educational reformations around the globe have been structured to address challenges in the attainment of learning objectives that surpass content and topic characterisation. The notion of mathematical competency signifies such objectives. In spite of having variations in the idea and definition of mathematical competency, one common construct is to have an ability to apply mathematics to solve problems in everyday situation. Many international mathematics assessments have provided a platform to children from different countries to get them assessed and know how much competent they are in solving unseen mathematical problems in everyday situations. There is a great need to identify which mathematics competencies a child should have and what the issues and challenges in achieving these competencies are. The idea of these competencies cannot be perceived in isolation. It should be backed up by strong theoretical framework and other integral aspects of mathematics education that are vital as per various studies. The aim of this paper is to explore the idea of mathematics education based upon building mathematical competencies among children and an assessment commensurate to that which may help policymakers in achieving the goal of preparing mathematically competent children who are able to apply mathematics to solve real life problems.